Life Cycle Assessment of Microalgae-Based Products for Carbon Dioxide Utilization in Thailand: Biofertilizer, Fish Feed, and Biodiesel [version 3; peer review: 2 approved] - Abigail Schudel; Cameron Morris; Adeel Rafiq; Shabbir Gheewala (F1000Research)
Background Microalgae-based products offer a sustainable solution for food, fuel, and agricultural inputs, presenting environmental benefits and economic opportunities. A comprehensive assessment is needed to understand their potential in supporting sustainability goals, considering the complex interplay between production methods, energy sources, and environmental impacts. Methods This study evaluated the environmental impacts of three microalgae-derived products – biodiesel, fish feed, and biofertilizer – through a comprehensive life cycle assessment. Nine scenarios were explored comparing three electricity profiles (current Thai mix, 50% renewable/50% current mix hybrid, 100% renewable) across the three products. The assessment evaluated environmental impacts and potential economic benefits of transitioning to these microalgae-based alternatives. Results and discussion All products demonstrated potential for significant environmental benefits under increased renewable energy scenarios. Fish feed consistently exhibited the lowest environmental impacts across all categories examined, showing substantial improvements with increased renewable energy use. With an annual demand of 0.4 million tonnes, fish feed could generate USD 560 million in revenue and reduce CO2 emissions by 1.1 million tonnes. Fulfilling the projected biodiesel demand of 4,015 million liters per year through microalgae production could yield approximately USD 3.5 billion in revenue and reduce CO2 emissions by 30 million tonnes compared to conventional fossil-based diesel. Additionally, algal biofertilizer production could meet a 5 million tonnes annual demand, offering USD 2 billion in revenue while reducing CO2 emissions by 6 million tonnes yearly. Collectively, these products could offset 37 million tonnes of CO2, representing about 14% of Thailand’s total CO2 emissions, contributing significantly to the country’s Nationally Determined Contribution (NDC) target of 20-30% greenhouse gas emissions reduction. Conclusion Transitioning to microalgae-based products could transform the aquaculture, energy, and agricultural sectors, potentially supporting the national climate change mitigation goals, if implemented.